PENGOLAHAN LIMBAH HASIL PERAIRAN (UDANG) MENJADI OLAHAN PETIS - Ayu Anggraeni Cahya Pitaloka; Rida Samsahas (AGROTERAP : Prodi Agroindustri Universitas 17 Agustus 1945 Surabaya, 2023)
Petis is a fermented processed product that has a thick and elastic texture, which is black or brown in color depending on the ingredients used. Shrimp paste is made from shrimp broth which is added with a thickening agent such as tapioca flour or cornstarch and other additive. Petis can also be categorized as a semi-moist food which has a moisture content of around 10-40%, an Aw value (water activity) of 0.65-0.90, and has a thick texture.